Progress and prospects in magnesium alloy scrap recycling - Lipeng Wang; Dong Liang; Rong Yu; Meng Wang; Yang Tian; Tingzhuang Ma; Bin Yang; Baoqiang Xu; Wenlong Jiang (Journal of Magnesium and Alloys)
Magnesium (Mg) alloy is widely used in aerospace and automotive industries as an excellent lightweight metal material to reduce carbon emissions. The expansion of Mg alloy applications and the increasing demands for these materials have significantly facilitated the generation of Mg alloy scrap. The recycling of Mg resources is crucial for promoting both environmental sustainability and economic viability. However, current recycling effect is unsatisfactory. Therefore, this paper provides a comprehensive review of the entire recycling process, including scrap classification, separation and sorting, pre-treatment, and recycling. This paper explores the generation of Mg alloy scrap and its reincorporation into industrial products. This review outlines various Mg scrap recycling technologies based on different phase states. These include liquid-state recycling (such as flux refining, impurity removal additives, fluxless refining, compound treatment, and direct remelting), solid-state recycling (involving hot extrusion, equal-channel angular pressing (ECAP), friction stir extrusion (FSE), and spark plasma sintering (SPS)), vapor-state recycling (comprising vacuum distillation and sublimation), electrochemical recycling (solid oxide membrane (SOM) electrolysis, RE-12™ electrorefining, and non-aqueous solution electrorefining), and Mg secondary alloy development. The advantages and existing challenges associated with each method are compared and discussed, and the current obstacles to the future recycling of complex scrap are examined.